The Wasteland of Nature. Human Existence between Junk and Utopias of Reintegration - Cuozzo, Gianluca (Religija ir kultūra, 2014)
To live in today’s disfigured landscape – where nature is but a fragment of an ancient beauty and richness – means entering the era of allegory tout court, within which human existence is forced to dwell in a lunar landscape remindful of those described by P. K. Dick, the locus of rotting refuse, where everything is swiftly reduced to “kipple” and “gubble.” Yet, despite being a mere fragment, an allegory of its former self, nature still retains a historical dimension: that dimension of time which the social universe – turned into an obtuse self-perpetuating myth – has given up in the name of the “always identical and always new” and of the irrevocability of a particular historical-contingent outcome. Yet, even a disfigured nature can be the source of a concrete utopia of reintegration, by virtue of its historical dimension. In other words, neither the wasteland of nature nor our dreams of salvation are exempt from an otherwise unsuspected mutual solidarity: being interconnected, they push imagination into remote and long forgotten lands where a happiness dwells, whose name – now unsayable in history – is Paradise regained.
Keywords: nature; consumerism; residuality; utopias of reintegration